T-2 toxin induces senescence in human neuroblastoma SH-SY5Y cells by regulating the HIF-1α/p53/p21 pathway - Yating Wang; Xu Wang; Qinghua Wu (Ecotoxicology and Environmental Safety)
The mechanisms by which T-2 toxin induces senescence in neurons, along with the involvement of hypoxia-inducible factor-1α (HIF-1α), remain poorly understood. Using human neuroblastoma SH-SY5Y cells as a model, T-2 toxin (6 nM, 1–48 h) induced senescence in SH-SY5Y cells, leading to cell cycle arrest. This was mediated by the upregulation of proteins involved in cell cycle regulation and stimulation of IL-6 and NF-κB expression. T-2 toxin rapidly triggered the expression of senescence-associated β-galactosidase, disrupted mitochondrial function, and altered the levels of Alzheimer’s disease-associated proteins (Tau, p-Tau, and APP). T-2 toxin also transiently elevated HIF-1α levels. Notably, HIF-1α regulated the expression of cell cycle inhibitory proteins (p16, p21, p53) and senescence-associated secretory phenotype factors (IL-8, IL-6, CCL2), along with the expression of senescence-associated β-galactosidase, thereby exacerbating T-2 toxin-induced cellular senescence. These findings underscore the vital role of HIF-1α in T-2 toxin-induced senescence in SH-SY5Y cells.